Shared and distinct functional connectivity of hippocampal subregions in schizophrenia, bipolar disorder, and major depressive disorder - Song, Yanzhuo; Yang, Jingyu; Chang, Miao; Wei, Yange; Yin, Zhiyang; Zhu, Yue; Zhou, Yuning; Zhou, Yifang; Jiang, Xiaowei; Wu, Feng; Kong, Lingtao; Xu, Ke; et al. (Frontiers in Psychiatry, 2022)
Schizophrenia (SZ), bipolar disorder (BD), and major depressive disorder (MDD) share etiological and pathophysiological characteristics. Although neuroimaging studies have reported hippocampal alterations in SZ, BD, and MDD, little is known about how different hippocampal subregions are affected in these conditions because such subregions, namely, the cornu ammonis (CA), dentate gyrus (DG), and subiculum (SUB), have different structural foundations and perform different functions. Here, we hypothesize that different hippocampal subregions may reflect some intrinsic features among the major psychiatric disorders, such as SZ, BD, and MDD. By investigating resting functional connectivity (FC) of each hippocampal subregion among 117 SZ, 103 BD, 96 MDD, and 159 healthy controls, we found similarly and distinctly changed FC of hippocampal subregions in the three disorders. Crucially, subregional specificity was found in the FC among the different hippocampal subregions. Furthermore, we found that the altered FC value was significantly correlated with clinical characteristics. Our findings suggest that the abnormal function of anterior cingulate cortex, middle frontal gyrus, and middle temporal gyrus might be a core feature of the psychopathological mechanisms of SZ, BD, and MDD. Our work also implies that the inferior orbital frontal gyrus and supplemental motor area might have shared abnormalities in SZ and BD, while caudate might be the differentiating feature of SZ. In addition, the different hippocampal subregions also play different roles in both the shared and the distinct changes in the three psychiatric disorders; CA and DG showed more similar functions than SUB. Our study provides evidence for the different functions of different hippocampal subregions in psychiatric pathology.